Knowledge, Attitude, and Practice of Adverse Drug Reaction Reporting among Community Pharmacists in India: A Review - J, Veena H.; Thaiseem, Afra; Ghore, Adarsh D.; Rihan, Mohammed; Abhishek, Y.; Yukthesh, E. S. (Journal of Pharmacy Practice and Community Medicine)
Adverse Drug Reaction (ADR) reporting plays a vital role in pharmacovigilance and patient safety. This review synthesizes published Indian studies examining the Knowledge, Attitude, and Practice (KAP) of community pharmacists regarding ADR reporting and their role within the Pharmacovigilance Programme of India (PvPI). While pharmacists generally acknowledge the importance of ADR reporting and express positive attitudes toward participating, significant gaps remain in knowledge of pharmacovigilance systems and actual reporting practices. Barriers such as limited awareness, inadequate training, perceived time constraints, and fear of legal consequences persist. Evidence from educational interventions suggests that structured training significantly improves knowledge and willingness to report. Strengthening training systems, simplifying reporting processes, and enhancing collaborative structures between community pharmacies and PvPI are essential to improving ADR reporting practices. Overall, empowering community pharmacists can enhance postmarketing drug safety surveillance and reduce preventable medication-related harm.
Keywords: ADR Reporting; Community Pharmacists; KAP; Pharmacovigilance; PvPI